Implementasi Kebijakan Program Bantuan KIP untuk Meningkatkan Tanggung Jawab Pemerintah di Desa Kalisongo Kecamatan Dau Kabupaten Malang - Willy Tri Hardianto; Asih Widi Lestari; Eli Susanti Debora (Public Administration Dept, Faculty of Social and Political Science, 2022)
On November 3rd, 2014 President Jokowi launched his inaugural program, namely the Healthy Indonesia Card (KIS), The Smart Indonesia Card (KIP) and the Prosperous Family Card (KKS). KIP (the smart Indonesia card) is a card for poor families who want to go to school and chosen by the Government, with KIP Program, it expected the dropout rate will decrease. In the Smart Indonesia Card Program (KIP), it is stored in the card and then the government regularly provides free cash funds to children in need, including school children with Social Welfare Problems and school children from underprivileged families who have not been guaranteed. The research purposes is to describe the implementation process through the implementation of the KIP assistance program policy to increase the government responsibility and to find out the factors arising from the KIP policy program for school children who need KIP in Kalisongo Village, Dau District, Malang Regency. The success of a policy implementation will be determined from existence interrelated factors and variables with Van Metter and Van Horn model theory. The KIP program can provide the opportunities to improve educational standards for children in need through the distribution of KIP funds and can reduce public's different and diverse mindset in recognizing the KIP program.